A Hardware Approach of a Low-Power IoT Communication Interface by NXP FlexIO Module - Chrastecky, Libor; Konecny, Jaromir; Stankus, Martin; Prauzek, Michal (Elektronika ir Elektrotechnika, 2019)
This article describes implementation possibilities of specialized microcontroller peripherals, as hardware solution for Internet of Things (IoT) low-power communication, interfaces. In this contribution, authors use the NXP FlexIO periphery. Meanwhile, RFC1662 is used as a reference communication standard. Implementation of RFC1662 is performed by software and hardware approaches. The total power consumption is measured during experiments. In the result section, authors evaluate a time-consumption trade-off between the software approach running in Central Processing Unit (CPU) and hardware implementation using NXP FlexIO periphery. The results confirm that the hardware-based approach is effective in terms of power consumption. This method is applicable in IoT embedded devices.